Persepsi Orang Tua Mengenai Pelaksanaan Pendidikan Kesehatan Reproduksi Untuk Anak Usia Dini - Sylva Alkornia (International Consortium of Education and Culture Research Studies, 2018)
This study aims to know the perceptions of parents against the implementation of reproductive education early childhood influenced him in OLD and Integrated Construction of LCS Bondowoso. The subject of the research is done to the 6 early childhood parents who have children ages 2-4 years and 2 informants, namely early childhood educators and community leaders. This research using qualitative research approach. The data collection method used is the method of interviewing, observation, and documentation. Research results on the implementation of the education of KesPro AUD influenced by 10 benchmark penmas i.e. citizens studying yeast, learning, learning resources, learning activities, teachers ' associations, places of learning, learning tools, learning, learning programs, and learning outcomes . So concluded the implementation of activities on early childhood education KesPro in OLD and Integrated Construction of LCS Bondowoso has not been fully implemented by either. Factors impeding the course of the implementation of the activities of the tutorials, namely (a) the old leaders of the citizens learn difficult split time to keep her son's learning activities with work, and (b) the limitations of the information and knowledge Organizer and mother on the implementation of the learning activities of KesPro early childhood so that required the presence of training or direction from the parties concerned.